1993
DOI: 10.1007/bf01710529
|View full text |Cite
|
Sign up to set email alerts
|

Topical antimicrobial prophylaxis of nosocomial pneumonia in mechanically ventilated patients. Microbiological observations

Abstract: Generally, reduction of colonization and infection with potentially pathogenic microorganisms in intensive care units (ICU) is attempted by a combination of antimicrobial agents administered topically in the digestive tract and systematically. We tested the efficacy of topical antimicrobial prophylaxis of the oropharynx and stomach administered in combination with sucralfate without systemic prophylaxis in 25 mechanically ventilated ICU patients. The regimen successfully reduced colonization with potentially p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 7 publications
2
16
0
Order By: Relevance
“…This has been suggested by others (7,10,21,25) and by us (4,5). Two placebo-controlled SDD trials, using colistin and tobramycin for topical prophylaxis, reported increased rates of infection with gram-positive cocci in patients receiving SDD (7,10).…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…This has been suggested by others (7,10,21,25) and by us (4,5). Two placebo-controlled SDD trials, using colistin and tobramycin for topical prophylaxis, reported increased rates of infection with gram-positive cocci in patients receiving SDD (7,10).…”
Section: Discussionmentioning
confidence: 62%
“…In the first study, eligible patients were included consecutively, whereas patients were chosen at random in the second study. The results of both studies have been published elsewhere (2,4). TAP medication consisted of (i) a suspension of tobramycin (8 mg/ml) and colistin (5 mg/ml), 1 ml of which was administered in each nostril and 5 ml of which was administered through a nasogastric tube; (ii) an application of tobramycin-colistin-amphotericin B (2%) in Orabase to the oropharynx; (iii) a suspension of amphotericin B (100 mg/ml), of which 0.5 ml was administered in each nostril and 2.5 ml was administered through a nasogastric tube; and (iv) 1 g of sucralfate suspension through a nasogastric tube.…”
Section: Methodsmentioning
confidence: 99%
“…C. indologenes -associated infection was first reported in 1993 in a patient with ventilator-associated pneumonia 5. Since then, Chryseobacterium has been reported to cause primary bacteraemia, catheter-related bacteraemia, wound sepsis, cellulitis, pyelonephritis, peritonitis, biliary tract infection, urinary tract infection, pneumonia and keratitis of the eye.…”
Section: Discussionmentioning
confidence: 99%
“…C indologenes has been reported to cause primary bacteraemia,9 13 catheter-related bacteraemia,7 10 11 15 wound sepsis,13 16 cellulitis,17 pyelonephritis,13 peritonitis,13 biliary tract infection,13 urinary tract infection,18 pneumonia13 14 and keratitis of the eye 19. Infections caused by all Chryseobacterium species combined represent only 0.03% of all bacterial isolates collected by the SENTRY Program during the 5-year period evaluated (1997–2001) with about 40% due to C indologenes 20.…”
Section: Discussionmentioning
confidence: 99%
“…Only about 10 of the reported cases of C indologenes seem to have occurred outside of Asia, including few in the USA 7 15 17. Most of the infections have been associated with indwelling devices, especially intravascular catheters and mechanical ventilators 7 10 11 14 15 18. However, removal of the indwelling device was not required for successful treatment in a number of the reported cases 22 23…”
Section: Discussionmentioning
confidence: 99%